Calycosin inhibits oxidative stress-induced cardiomyocyte apoptosis via activating estrogen receptor-α/β. Issue 1 (1st January 2016) - Liu, Bin; Zhang, Jingzhi; Liu, Weihua; Liu, Ningning; Fu, Xiuqiong; Kwan, Hiuyee; Liu, Shaojun; Liu, Benrong; Zhang, Shuangwei; Yu, Zhiling; Liu, Shiming
Graphical abstract: Abstract: Oxidative stress-induced myocardial apoptosis is a key step in the pathogenesis of ischemic heart disease. Calycosin is a phytoestrogen extracted from Radix astragali. In this study, we examined the effects and mechanisms of calycosin on oxidative stress-induced myocardial apoptosis. Molecular docking showed that calycosin can couple into binding site of ERα and β. Pretreatment with calycosin increased the expression levels of ERα and β. In H9C2 cells, H2 O2 reduced cell viability and induced apoptosis, however, calycosin diminished the effects of H2 O2 in a dose-dependent manner. Pretreatment with ICI 182, 780, an estrogen receptor inhibitor, negated the protective effect of calycosin against H2 O2 -induced apoptosis. In addition, Akt phosphorylation was upregulated by calycosin mono treatment and downregulated by co-treatment with calycosin and ICI 182, 780. These data demonstrated that calycosin exhibits anti-apoptotic effects by activating ERα/β and enhancing Akt phosphorylation in cardiomyocytes.